Social Responsibility and Covid-19 health crisis: communication of Spanish energy companies on Twitter - Zeler, Ileana (2022)
Corporate Social Responsibility (CSR) is considered a legitimizing activity for organizations and an essential value for reputation fundamentally in crises. Social networks, especially Twitter, are beneficial tools for CSR communication. This social network is considered the ideal tool for communication management during critical situations. Thus, the main objective of this research is to analyze how the most responsible companies in the Spanish energy sector communicate their CSR actions and policies during the pandemic on Twitter. Through the content analysis of 3,146 tweets published during 12 months, the study evaluates the activity, topics and communicative approach of CSR messages posted during the health crisis. Despite the pandemic situation, the results suggest that organizations have not significantly changed their roadmap in the communication of their CSR actions.